Acceptability of hospital diets by patients admitted to a university hospital (Research, Society and Development, 2021)
Hospital diets aim to meet the demands of patients arising from the nutritional and pathophysiological status in which they find themselves, and it is important to consider the individuality of each patient to prescribe a diet that meets the nutritional needs, and, for this, factors such as weight, height, caloric requirements, macronutrient distribution, nutrient restriction, food habits and preferences. The present study aimed to evaluate the acceptability of oral diets provided at a university hospital. This is a population-based study with a quantitative, observational and descriptive approach. The evaluation of the acceptance of diets was carried out through a questionnaire with closed questions regarding the degree of acceptance of the diets offered according to small and large meals, with variables for classification and control of food intake. The collected data were tabulated with the help of the SPS S 22.0 SOFTWARE and the referring EXCEL, and through these tables and graphs were constructed, in order to have a better understanding of the results obtained. Data analysis was performed using descriptive statistics with mean measurements, frequency measurements and non-parametric statistics with the Chi-square test, considering a significance level of 95% and a 5% margin of error. Values of p